The measurement of consensus in pair-comparison studies - Campos, Leonel (1969)
It is suggested that Kendall's coefficient of agreement, u, is not an appropriate measure of consensus in pair-comparison studies. A new index of consensus, M(c), is described. It is further suggested that Kendall's own adaptation of the X2 may be used, with minor modifications, to test the significance of a departure of M(c) from a value of zero.
Includes bibliographical references (page 38).